2017
DOI: 10.18632/oncotarget.22566
|View full text |Cite
|
Sign up to set email alerts
|

G6PD promotes renal cell carcinoma proliferation through positive feedback regulation of p-STAT3

Abstract: Ectopic Glucose 6-phosphate dehydrogenase (G6PD) expression plays important role in tumor cell metabolic reprogramming and results in poor prognosis of multiple malignancies. Our previous study indicated that G6PD is overexpressed in clear cell renal cell carcinoma (ccRCC), the most common subtype of RCC. However, its role in RCC is still unclear. Here, we demonstrate that G6PD is not only up-regulated in all types of RCC specimens but also displays higher activities in RCC cell lines. G6PD overexpression prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
84
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(100 citation statements)
references
References 53 publications
14
84
2
Order By: Relevance
“…It has been reported that G6PD serves key roles in reactive oxygen species (ROS) accumulation. Previous results from our laboratory demonstrated that G6PD could promote ROS generation by increasing NADPH oxidase 4 activity in ccRCC (16). Furthermore, increased oxidative stress is an important factor leading to abnormal intracellular signal transduction (17,18).…”
Section: G6pd Facilitates Clear Cell Renal Cell Carcinoma Invasion Bymentioning
confidence: 82%
See 4 more Smart Citations
“…It has been reported that G6PD serves key roles in reactive oxygen species (ROS) accumulation. Previous results from our laboratory demonstrated that G6PD could promote ROS generation by increasing NADPH oxidase 4 activity in ccRCC (16). Furthermore, increased oxidative stress is an important factor leading to abnormal intracellular signal transduction (17,18).…”
Section: G6pd Facilitates Clear Cell Renal Cell Carcinoma Invasion Bymentioning
confidence: 82%
“…Furthermore, G6PD can cooperate with numerous signaling pathways in order to promote cancer, and G6PD was reported to be overexpressed in various types of tumor, including breast carcinoma, ccRCC and lung adenocarcinoma (13)(14)(15). Previous work from our laboratory described the prognostic significance of G6PD in ccRCC, and demonstrated its role in promoting tumor growth through positive feedback regulation of phospho-signal transducer and activator of transcription 3 (p-STAT3) (14,16). However, G6PD ability to promote ccRCC invasion remains unknown.…”
Section: G6pd Facilitates Clear Cell Renal Cell Carcinoma Invasion Bymentioning
confidence: 99%
See 3 more Smart Citations